Peran Guru Pendidikan Agama Kristen sebagai Konselor dalam Membentuk Perilaku Sosial Siswa - Crisena Crisena; Firiska Yulinata Nababan; Naomi Yolanti Octavia Ritonga; Novita Ester Marlina Zebua (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
This study aims to analyze the role of Christian Religious Education (CRE) teachers as counselors in shaping students’ social behavior amid increasing behavioral deviations such as bullying, violence, misuse of social media, and low tolerance. These phenomena are influenced by internal factors such as emotional instability and identity formation, as well as external factors including family, environment, and digital culture. This research employs a descriptive qualitative method using a library research approach by collecting data from books, scholarly journals, and relevant documents. The findings reveal that CRE teachers play a strategic role not only as educators but also as counselors who accompany students holistically, covering spiritual, moral, emotional, and social aspects. The counseling role performed by CRE teachers includes modeling behavior, mediating conflicts, strengthening self-control, providing social support, and building empathetic relationships with students. Through this approach, students undergo a process of internalizing Christian values such as love, forgiveness, responsibility, and tolerance, which contribute to the development of positive social behavior. Furthermore, collaboration among teachers, parents, and the community serves as a supporting factor in successful character formation. Therefore, the role of CRE teachers as counselors is proven to be effective in shaping students’ social behavior in accordance with moral, social, and religious values, while contributing to the development of a generation with integrity and competitiveness.